OBSTACLE IN ENGLISH ORAL DISCOURSE AT THE 3RD SEMESTER STUDETS OF ENGLISH EDUCATION FACULTY OF UNIVERSITAS RIAU KEPULAUAN BATAM IN ACADEMIC YEAR 2014-2015 - Fasaaro Hulu (BASIS (Bahasa dan Sastra Inggris), 2015)
This research aims to find out the Obstacle in English oral discourase faced by the 3rd semester students of Universitas Riau Kepulauan. To get the result A qualitatif methods applies in the research by using open questioner. The students of Universitas Riau Kepulauan have several obstacle in English speaking which are influenced by the lecturers, the students, the methods, material, lack of time, lack of vocabulary, lack of grammar and others. there are 140 data found from the students. The data related to the lecturers are 3 data, from the material are 3 data, from the methos are 6 data, from the grammar are 48 data, from the vocabulary are 22 data, cognitive are 14 data, psycomotor are 22 data, affective ara 4 data, time are 3 data. the data are analysed and described in the form of the table that follow by the explanation for each data from the table.